2010
DOI: 10.1002/mabi.200900390
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Crosslinking of L‐DOPA Containing Polypeptide Vesicles

Abstract: The synthesis and self-assembly of DOPA containing diblock copolypeptides into spherical vesicles is described. DOPA residues are naturally abundant in mussel adhesive proteins and are responsible for extensive covalent crosslinking of these materials upon oxidation. We found that vesicles could be formed from copolypeptides containing different amounts of DOPA substituted into hydrophobic segments, up to 100% DOPA content. The DOPA containing vesicles were covalently crosslinked in water using an oxidizing ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…In 2010, Deming's lab reported the preparation of lysinedihydroxyphenylalanine (i.e. K 60 DOPA 20 ) based vesicles, where the hydrophobic DOPA segments have the added feature of being sensitive toward oxidation [95]. DOPA residues are found naturally in mussel byssus and are important components in the ability of byssal threads to adhere underwater and to crosslink into rigid networks [96].…”
Section: Insert Figurementioning
confidence: 99%
“…In 2010, Deming's lab reported the preparation of lysinedihydroxyphenylalanine (i.e. K 60 DOPA 20 ) based vesicles, where the hydrophobic DOPA segments have the added feature of being sensitive toward oxidation [95]. DOPA residues are found naturally in mussel byssus and are important components in the ability of byssal threads to adhere underwater and to crosslink into rigid networks [96].…”
Section: Insert Figurementioning
confidence: 99%
“…In the early 2000s, Lecommandoux et al 38 and Deming et al [39][40][41] reported on the successful preparation of vesicles from self-assembling, amphiphilic, polypeptide-based block copolymers.…”
mentioning
confidence: 99%
“…However, these surfactants consist of amino acids polymerized into polydisperse blocks and then appended to make copolymers. Different amino acids have been blended into each block with set average composition, but the precise sequence of amino acids in each block could not be controlled (8). Amino acid copolymerization prevents the direct incorporation of specific peptide sequences, which are required for recognition and targeting in biology.…”
mentioning
confidence: 99%